The determinants of India$1 (Bs national military strategys - Sharma, Rakesh (U.S.I. Journal)
The enunciation of a nation$1 (Bs short and long-term security strategies is dependent on the geo-strategic environment. Conversely, failure of security strategies is also due to inappropriate assessment of the environment.1 Therefore, in order to formulate a long-term military strategy, it is imperative to have holistic visualisation of the principal regional threats and challenges, including asymmetric ones, transnational threats, and even unanticipated ones! India is geographically located in a challenging strategic environment which argues for a strong and effective military force capable of defending territorial integrity and sovereignty. In a democratic dispensation like India, conduct of a military campaign will always be a political decision dictated by security considerations which are interpreted through a political lens.- Reproduced s